Leveraging enhanced perceptual markings for accident prevention in long-range applications near freeway exits: Evidence from driving simulation experiments - Jingjing Zhang; Naikan Ding; Shuhao Wu; Guangyao Huang; Linsheng Lu (PLoS ONE, 2025)
Perceptual markings are extensively applied in practice for accident prevention, especially at the high-risk segments and/or sites, such as the freeway exits. However, most of the present perceptual markings are tested for a short-range of segment, which could hardly guide its practical application in real-world scenarios, such as the freeway exits. The long-range application and performance of them are barely rigorously investigated in previous research, and how to effectively accommodate the cost-effective perceptual markings in the long-range application is unaddressed. Given this, we proposed a novel perceptual marking form, i.e., enhanced linear perspective markings (ERLPMs) in fixed-angle or variable-angle patterns, by add appropriate gaps between adjacent marking groups, to accommodate the long-range application on freeways. A series of driving simulation experiments were conducted to test the performance of the ERPLMs on adjusting drivers’ speed, acceleration, distance and time headways. The results show that 1) the ERLPMs effectively led to significant reduction of speed and increase in headways while vehicles approaching the exits in a long-range segment; 2) the greatest speed reduction (0.40 m/s), acceleration reduction (0.22 m/s2), distance headway increase (10.75 m), and time headway increase (0.41 s) were observed as compared with the baseline (no extra markings); and 3) the fixed-angle pattern with θ=120∘ had the most impressive and stabilized performance on the speed and headway control aspects. The findings of the study suggest that the ERLPMs are capable of adjusting driver behaviors smoothly and bring substantial benefits for accident prevention at freeway exit area, which could be a support for the practical usage of various markings in the long-range on freeways.